Home‐based physical activity after treatment for esophageal cancer—A randomized controlled trial - Poorna Anandavadivelan; Kalle Malberg; Karin Vikstrom; Sandra Nielsen; Ulrika Holdar; Asif Johar; Pernilla Lagergren (Cancer Medicine)
Abstract Background The treatment of most esophageal cancer patients includes chemo(radio)therapy and extensive surgery, causing physical decline with loss of muscles. This trial aimed to test the hypothesis that a tailored home‐based physical activity (PA) intervention improves muscle strength and mass in patients having undergone curative treatment for esophageal cancer. Methods Patients operated for esophageal cancer 1 year earlier were included in a nationwide randomized controlled trial in Sweden in 2016–2020. The intervention group was randomized to a 12‐week home‐based exercise program, while the control group was encouraged to maintain routine daily PA. The primary outcomes were changes in maximal/average hand grip strength measured with hand grip dynamometer and lower extremity strength measured using 30‐second chair stand test and muscle mass measured using a portable bio‐impedance analysis monitor. Intention‐to‐treat analysis was used, and results were presented as mean differences (MDs) with 95% confidence intervals (CIs). Results Among 161 randomized patients, 134 completed the study, 64 in the intervention group and 70 in the control group. Compared with the control group (MD 2.73; 95% CI 1.75–3.71), patients in the intervention group (MD 4.48; 95% CI 3.18–5.80) had statistically significantly (p = 0.03) improved lower extremity strength. No differences were seen for hand grip strength or muscle mass. Conclusion A home‐based PA intervention 1 year after surgery for esophageal cancer improves lower extremity muscle strength.